PARTICIPATION OF FACTIONS OF POLITICAL PARTIES IN THE PROCESS OF PARLIAMENTARY OVERSIGHT - Bekov Ikhtiyor Rustamovich (Scholar Express Journals, 2023)
This article explores Factions of political parties are an important subject of parliamentary control in the Republic of Uzbekistan, as well as, in the direction of the importance of reforms in the political sphere of the Republic of Uzbekistan over the past three years
Keywords: Political party; faction; party groups; elections